Detection of let-7 miRNAs in urine supernatant as potential diagnostic approach in non-metastatic clear-cell renal cell carcinoma - Fedorko, Michal; Juracek, Jaroslav; Stanik, Michal; Svoboda, Marek; Poprach, Alexandr; Buchler, Tomas; Pacik, Dalibor; Dolezel, Jan; Slaby, Ondrej (Biochemia medica, 2017)
INTRODUCTION: Urinary microRNAs (miRNAs) are emerging as a clinically useful tool for early and non-invasive detection of various types of cancer. The aim of this study was to evaluate whether let-7 family miRNAs differ in their urinary concentrations between renal cell carcinoma (RCC) cases and healthy controls. MATERIALS AND METHODS: In the case-control study, 69 non-metastatic clear-cell RCC patients and 36 gender/age-matched healthy controls were prospectively enrolled. Total RNA was purified from cell-free supernatant of the 105 first morning urine specimens. Let-7 family miRNAs were determined in cell-free supernatant using quantitative miRNA real-time reverse-transcription PCR and absolute quantification approach. RESULTS: Concentrations of all let-7 miRNAs (let-7a, let-7b, let-7c, let-7d, let-7e and let-7g) were significantly higher in urine samples obtained from RCC patients compared to healthy controls (P < 0.001; P < 0.001; P = 0.005; P = 0.006; P = 0.015 and P = 0.002, respectively). Subsequent ROC analysis has shown that let-7a concentration possesses good ability to differentiate between cases and controls with area under curve being 0.8307 (sensitivity 71%, specificity 81%). CONCLUSIONS: We have shown that let-7 miRNAs are abundant in the urine samples of patients with clear-cell RCC, and out of six let-7 family members, let-7a outperforms the others and presents promising non-invasive biomarker for the detection of RCC.
Keywords: regulace genové exprese u nádorů; dospělí; Female; Adult; ženské pohlaví; Gene Expression Regulation, Neoplastic; lidé; karcinom z renálních buněk; Aged, 80 and over; polymerázová řetězová reakce s reverzní transkripcí; Kidney Neoplasms; Carcinoma, Renal Cell; ROC křivka; Male; Reverse Transcriptase Polymerase Chain Reaction; nádorové biomarkery; Aged; mikro RNA; nádory ledvin; Biomarkers, Tumor; lidé středního věku; MicroRNAs; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; ROC Curve; Humans